The role of sustainable development principles in promoting environmental and disaster legislation - El-Agha, Mohamed Ramadan (Journal of Risk and Crisis Management, 2019)
The study aims at linking disaster and environmental management and its laws with the principles of sustainable development. This is to get the fastest and best result at the lowest cost and effort in the future sustainable development efforts. The researcher used the analytical descriptive methodology to describe laws and legislations including the Islamic law، and the principles of sustainable development، and the level of interdependence between their different components.The study concluded that there is a strong link between the components of sustainable development، environmental management and disaster management. These include protection of life with high quality، human resource protection and risk reduction. That is to strengthen the scientific and practical foundations for implementing a comprehensive preventive system. Environmental، disaster management and laws، on one hand، and sustainable development on the other، both in regulations and laws، or through various practices، coincide with Islamic law and the principles of sustainable development.
Keywords: sustainable development; environmental legislation; disaster legislation